Arthroscopic Suture and Transfemoral Fixation for Acute Posterior Cruciate Ligament Femoral Avulsion Fracture - Xian Zhang, M.D.; Bo Ren, Ph.D., M.D. (Arthroscopy Techniques)
Acute posterior cruciate ligament (PCL) femoral avulsion fractures in adults are rare. This is a very specific injury often diagnosed with magnetic resonance imaging to evaluate PCL continuity, and avulsion fractures are evaluated preoperatively via 3-dimensional computed tomography. We describe a modified technique for arthroscopic transfemoral suture of the PCL–femoral ligament combined with Versalok fixation to preserve the native femoral insertion of the PCL and ligament tension.